Prospective Teachers' Lived Experience on Computer-based Instructional Materials: A Phenomenological Study - Baytak, Ahmet; Hirca, Necati (Kamla-Raj Enterprises, 2013)
The purpose of this phenomenological study is to unveil the qualitative rather than the quantitative factors in student-teachers' experiences on instructional material development for their future classrooms. The participants of this study were nine student-teachers who took Science and Technology Teaching course at Classroom Teacher Program. The data sources of this qualitative analysis were the interview transcripts, observation notes, and developed materials. A careful analysis unveiled the following themes: lack of technical skills, lack of instructional design experiences and skills, peer influences, and feeling the novelty. The implications of these identified themes were found important for education community to effectively integrate new educational tools in lessons.
Keywords: Educational Technology; Computer-Aided Instructional Material; Teacher Training; Living Experience